Theoretical Investigation Including Averages Fusion Cross-Section, Reactivity for the D-D and D-3He Reactions - Basil, Asmaa; Majeed, Raad Hameed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Nuclear fusion technology for power production is considered a renewable and clean energy source, and it is used in many applications such as scientific research, systems for electrical energy production, and fast charge particles such as protons, alpha particles, electrons, beta particles, positrons, etc. In addition, there exists another application such as materials irradiation and artificial elements production. There exist more than 51 fusion reactions in nature. The most important thermonuclear fusion reactions are those used in one of the common hydrogen isotopes such as deuterium, the D-D and D-3He reactions. A laboratory fusion cross-section data fitting equations are calculated theoretically by using the least square fitting technique. Calculations include results for average cross-sections and the related fusion reaction reactivaties for the above two reactions.  Both reactions D-D and D-3He occur in the energy and or temperature range in between energetic ions coming from the measured Maxwellian distribution and atoms at rest.